Cellular communications systems in congested environments : resource allocation and end-to-end quality of service solutions with MATLAB - Ghorbanzadeh, Mo; Abdelhadi, Ahmed (Engineer); Clancy, Charles (Springer International Publishing, 2017)
This book presents a mathematical treatment of the radio resource allocation of modern cellular communications systems in contested environments. It focuses on fulfilling the quality of service requirements of the living applications on the user devices, which leverage the cellular system, and with attention to elevating the users? quality of experience. The authors also address the congestion of the spectrum by allowing sharing with the band incumbents while providing with a quality-of-service-minded resource allocation in the network. The content is of particular interest to telecommunications scheduler experts in industry, communications applications academia, and graduate students whose paramount research deals with resource allocation and quality of service.
Keywords: MATLAB.; Wireless communication systems.; Cell phone systems.; Quality of service (Computer networks); elektronické knihy; electronic books